Effects of Tityus serrulatus scorpion venom on lung mechanics and inflammation in mice - Paneque Peres, Ana Claudia; Nonaka, Paula Naomi; Camillo de Carvalho, Paulo de Tarso; Toyama, Marcos Hikari [UNESP]; Melo e Silva, Cesar Augusto; Vieira, Rodolfo de Paula; Dolhnikoff, Marisa; Zamuner, Stella Regina; Franco de Oliveira, Luis Vicente (Pergamon-Elsevier B.V. Ltd, 2009)
The present study evaluated the effects of an intramuscular injection of Tityus serrulatus venom (TsV) (0.67 mu g/g) on lung mechanics and lung inflammation at 15, 30, 60 and 180 min after inoculation. TsV inoculation resulted in increased lung elastance when compared with the control group (p < 0.001): these values were significantly higher at 60 min than at 15 and 180 min (p < 0.05). Resistive pressure (Delta P(1)) values decreased significantly at 30, 60 and 180 min after TsV injection (p < 0.001). TsV inoculation resulted in increased lung inflammation, characterised by an increased density of mononuclear cells at 15, 30, 60 and 180 min after TsV injection when compared with the control group (p < 0.001). TsV inoculation also resulted in an increased pulmonary density of polymorphonuclear cells at 15, 30 and 60 min following injection when compared to the control group (p < 0.001). In conclusion, T serrulatus venom leads to acute lung injury, characterised by altered lung mechanics and increased pulmonary inflammation. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Tityus serrulatus; Lung inflammation; Lung mechanics; Respiratory system